Human Responses to the Thermal Comfort in Air-Conditioned Building: A Climate Chamber Study - Jusoh, Norfadzilah; Ismail, Ahmad Rasdan; Md Zein, Raemy (International Journal of Integrated Engineering, 2022)
One of the challenges for engineers in designing comfort indoor environments is merging the need of energy savings and thermal comfort of the occupants. However, to assess complex heterogeneous environments created by novel building systems, there is a need for choosing more sophisticated and precise tools. There are many best ways to evaluate thermal comfort, at the same time the most cost and time-consuming one, various modelling tools are widely used.  In this paper, we present a human climate chamber as a methodology for indoor environmental research, to predict the thermal comfort. Along with presenting this methodology, the human climate chamber was demonstrated on ?ve supply temperature representing the indoor environment such as conditions for which thermal sensation was predicted with satisfactory accuracy. Based on the presented results, the overall thermal sensation on the body will be influenced mainly by those body segments that have a greatest thermal sensation under different condition's environment (supply temperature). The overall thermal comfort will follow the warmest environment (26 oC and 29 oC) and the coldest in a cool environment (19 oC and 23 oC). Furthermore, the overall thermal comfort will closely follow the parts of the body that feel the most uncomfortable in a cool or warm environment. The study found that supply temperature at the 23 oC indicates that the PMV is comfortable. The value of PMV in a supply temperature set at 23 oC is 0.26. This study contributes to the body knowledge of thermal comfort towards human in the building.